Thea Stilton and the Blue Scarab Hunt - Stilton, Thea (New York : Scholastic Inc., 2012)
An ancient treasure is in danger! The Thea Sisters have been invited to Egypt to participate in a fabumouse archeological excavation. They are helping to look for the legendary ancient Treasure of the Sun! A precious blue stone scarab may be the key to their search, and they work enthusiastically to uncover the past. But they also discover that thieves are after the hidden treasure. It's up to the Thea Sisters to stop them.
Translation of: Caccia allo scarabeo blu. "Based on an original idea by Elisabetta Dami"--Title page verso.
Translated from the Italian.
Ages 7-10.
Keywords: Egypt -- Juvenile fiction. -- Mice -- Juvenile fiction. -- Students -- Juvenile fiction. -- Theft -- Juvenile fiction. -- Stilton, Thea -- Fiction